Mixing Compost and Biochar Can Enhance the Chemical and Biological Recovery of Soils Contaminated by Potentially Toxic Elements - Matteo Garau; Maria Vittoria Pinna; Maria Nieddu; Paola Castaldi; Giovanni Garau (Plants, 2024)
Biochar and compost are able to influence the mobility of potentially toxic elements (PTEs) in soil. As such, they can be useful in restoring the functionality of contaminated soils, albeit their effectiveness can vary substantially depending on the chemical and/or the (micro)biological endpoint that is targeted. To better explore the potential of the two amendments in the restoration of PTE-contaminated soils, biochar, compost (separately added at 3% w/w), and their mixtures (1:1, 3:1, and 1:3 biochar-to-compost ratios) were added to contaminated soil (i.e., 2362 mg kg−1 of Sb and 2801 mg kg−1 of Zn). Compost and its mixtures promoted an increase in soil fertility (e.g., total N; extractable P; and exchangeable K, Ca, and Mg), which was not found in the soil treated with biochar alone. All the tested amendments substantially reduced labile Zn in soil, while biochar alone was the most effective in reducing labile Sb in the treated soils (−11% vs. control), followed by compost (−4%) and biochar–compost mixtures (−8%). Compost (especially alone) increased soil biochemical activities (e.g., dehydrogenase, urease, and β-glucosidase), as well as soil respiration and the potential catabolic activity of soil microbial communities, while biochar alone (probably due to its high adsorptive capacity towards nutrients) mostly exhibited an inhibitory effect, which was partially mitigated in soils treated with both amendments. Overall, the biochar–compost combinations had a synergistic effect on both amendments, i.e., reducing PTE mobility and restoring soil biological functionality at the same time. This finding was supported by plant growth trials which showed increased Sb and Zn mineralomass values for rigid ryegrass (Lolium rigidum Gaud.) grown on biochar–compost mixtures, suggesting a potential use of rigid ryegrass in the compost–biochar-assisted phytoremediation of PTE-contaminated soils.